KAJIAN PENERAPAN FREE SPACE OPTIC (FSO) PADA GEDUNG E DAN FG DI KAMPUS A UNIVERSITAS TRISAKTI - Ningsih, Yuli Kurnia; Surjati, Indra; Danubrata, Oky (Jurnal Teknik Elektro, 2007)
Free Space Optics (FSO) as Data Communication System technology contribute positivelynot only to its users but also to its operators. It is regarded as the development of infraredcommunication that can overcome some drawbacks of wireless data communication such aslosses. This study concerns the implementation of Free Space Optics for cross connectedbuildings with the calculation of link margin factor to determine exactly the resultingperformance under different kinds of weather: sunny, moderate rain and heavy rain. Theresults shown are those for the distance of 35.66 m. The obtained attenuation factors are asfollows: -0.0078452 dB in sunny weather, -0.0156904 dB in light rain; and -0.1412136 dB inheavy rain. These results are still less than the link margin of 32.2228 dB, which means thatFree Space Optics is good enough to be implemented. The result also showed that for thedistance of 118.79 m, the attenuation factor is -0.4704084 dB in heavy rain and still lessthan the link margin of 22.5524 dB. It means that Free Space Optics can be implemented forline of sight communication.Keywords: Free Space Optics (FSO), link margin, weather, attenuation factor